1996
DOI: 10.1093/brain/119.2.551
|View full text |Cite
|
Sign up to set email alerts
|

Stride length regulation in Parkinson's disease

Abstract: Results of our previous studies have shown that the slow, shuffling gait of Parkinson's disease patients is due to an inability to generate appropriate stride length and that cadence control is intact and is used as a compensatory mechanism. The reason for the reduced stride length is unclear, although deficient internal cue production or inadequate contribution to cortical motor set by the basal ganglia are two possible explanations. In this study we have examined the latter possibility by comparing the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
206
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 756 publications
(239 citation statements)
references
References 39 publications
16
206
1
6
Order By: Relevance
“…He suggested that the placement of visual cues perpendicular to the direction of gait spaced one step length apart were most effective in improving gait in patients with PD. Many single-session studies have confirmed the benefit of visual cues (high-contrast transverse floor lines) [21][22][23][24]. However these open-loop feedback systems may not have long-term effects [25] unless a dedicated physical training program is established, as demonstrated in a patient trained to walk on floor cues reaching 120 percent of the uncued stride length over a 1-month period [26].…”
Section: Discussionmentioning
confidence: 99%
“…He suggested that the placement of visual cues perpendicular to the direction of gait spaced one step length apart were most effective in improving gait in patients with PD. Many single-session studies have confirmed the benefit of visual cues (high-contrast transverse floor lines) [21][22][23][24]. However these open-loop feedback systems may not have long-term effects [25] unless a dedicated physical training program is established, as demonstrated in a patient trained to walk on floor cues reaching 120 percent of the uncued stride length over a 1-month period [26].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is quite surprising in the PD group, because the detrimental impact of secondary cognitive tasks on previously examined motor tasks, such as standing balance and gait, is robust [19]. It has been hypothesized that the reduction in gait performance and arrhythmicity of gait under a dualtask condition is due to individuals with PD recruiting attentional resources for gait, specifically the frontal-cortical regions, to compensate for the damaged automaticity of gait [20]. Because of limited cognitive resources and the neurodegenerative nature of the disease, the ability to recruit attentional resources is limited, particularly during a dual task and, as such, performance suffers.…”
Section: Groupmentioning
confidence: 99%
“…Despite the neuropathology of the disease, evidence suggests that individuals with PD are capable of improving their gait via motor learning strategies (Felix et al, 2012;Fok, Farrell, McMeeken, & Kuo, 2011;Pendt, Reuter, & Müller, 2011;Rochester et al, 2010;Werner & Gentile, 2010), as evidenced by the fact that exercise and movement strategy training have been found collectively to contribute to improvements in gait (Rochester, Nieuwboer, & Lord, 2011). For example, research focused on the nonpharmacological management of gait impairment in PD has found that the use of external cues is generally effective (Morris, Iansek, Matyas, & Summers, 1996;Rochester et al, 2010;Rochester et al, 2005;Spaulding et al, 2012).…”
mentioning
confidence: 99%
“…A potential drawback of this approach, however, is that these strategies typically require assistive devices (e.g., a cane with laser lights or listening devices with rhythmic auditory signals) that may be expensive and impractical in certain environments. Moreover, results have predominantly shown only short-term benefits of lab-based external cueing of this nature (Morris et al, 1996;Rochester et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation